EFISIENSI MESIN PEMBAKARAN DAN KINERJA SISTEM PEMANASAN BAHAN BAKAR MELALUI SISTEM PIPA KNALPOT - Azamataufiq Budiprasojo; Andik Irawan (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2017)
Exhaust Pipe Preheated Fuel System (EP2FS) is a fuel heating system that utilizes wasted heat from the exhaust. Heating the fuel aims to increase the homogeneity of the mixture of fuel and air to improve the combustion process in the engine. Making EP2FS requires careful design and calculation because the temperature of the fuel must not exceed 60 oC so as not to evaporate. The design and estimation use the helical heat exchanger (theory of heat transfer). The system that is ready will be applied in motorized vehicles to be tested for combustion efficiency and performance. Keywords: Fuel Preheating, Engine Performance, Helical Heat Exchanger